2000
DOI: 10.1177/002215540004800610
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor and Its Receptor in Cirrhotic Liver Disease

Abstract: Polypeptide growth factors, including epidermal growth factor (EGF), play a central role in regulating hepatocyte growth both in vivo and in primary culture. To characterize EGF gene expression in the pathogenesis of regenerative cirrhotic fibrosis, we employed biotinylated antisense oligonucleotide probes to localize hepatic mRNA transcripts in situ. In control tissue and regenerative hepatic nodules, EGF receptor (EGFR) mRNA transcripts were expressed constitutively. In contrast, oligonucleotide probes targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 46 publications
1
48
1
2
Order By: Relevance
“…38 The process of HSC activation is coupled with the sequential up-expression of receptors for growth factors, including PDGF-bR, type I & II receptors for TGF-b 39,40 and EGFR. 8 In addition, HSC activation coincides with a dramatic reduction in the abundance PPARg. [9][10][11] We previously proposed an antagonistic relationship between the activation of the signaling pathways for these growth factors and the gene expression of PPARg in HSC, that is, activation of the signaling pathways reduces the activity of PPARg by suppressing Figure 7 The blockade of the PI-3K/AKT, ERK, and/or JNK signaling pathways results in the induction of apoptosis, which is partially eliminated by the inhibition of PPARg activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The process of HSC activation is coupled with the sequential up-expression of receptors for growth factors, including PDGF-bR, type I & II receptors for TGF-b 39,40 and EGFR. 8 In addition, HSC activation coincides with a dramatic reduction in the abundance PPARg. [9][10][11] We previously proposed an antagonistic relationship between the activation of the signaling pathways for these growth factors and the gene expression of PPARg in HSC, that is, activation of the signaling pathways reduces the activity of PPARg by suppressing Figure 7 The blockade of the PI-3K/AKT, ERK, and/or JNK signaling pathways results in the induction of apoptosis, which is partially eliminated by the inhibition of PPARg activation.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9][10][11] Prior other studies have suggested the opposite functions of PDGF and PPARg in adipogenesis. 32,33 To evaluate the effect of activation of PDGF and EGF signaling on regulation of gene expression of PPARg, exogenous PDGF and EGF were added to passaged HSC for an additional 24 h after the treatment with or without curcumin in serum-free media for 24 h. PPARg expression was determined by realtime PCR and Western blotting analyses.…”
Section: Exogenous Pdgf or Egf Reduces Gene Expression Of Pparc Whicmentioning
confidence: 99%
See 1 more Smart Citation
“…EGF has been hypothesized to promote hepatocyte transformation, and dysregulation of the EGF signaling pathway has been speculated to be important in early hepatocarcinogenesis (29,30). To the best of our knowledge, numerous previously published genetic studies have demonstrated a positive association between the EGF 61A/G polymorphism and risk of HCC, while other studies have found no notable evidence that this polymorphism increases the susceptibility to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Inwieweit anderen profibrotischen Wachstumsfaktoren, wie z. B. PDGF (Pinzani et al 1996, Hoyle et al 1999, EGF (Kömüves et al 2000), CTGF (Pan et al 2001, Leask et al 2002), bFGF (Thornton et al 1992, Fibbi et al 1999) und IGF-1 (Saile et al 2004, Novosyadlyy et al 2006, die in anderen Organfibrosen nachgewiesen wurden, in der Pathogenese der equinen Endometrose eine möglicherweise größere Bedeutung zukommt, muss in nachfolgenden Studien geklärt werden.…”
Section: Diskussionunclassified